Kinerja Reproduksi Beberapa Jenis Sapi Potong di Kota Sawahlunto Provinsi Sumatera Barat: Reproductive Performance of Beef Cattle Breeds in Sawahlunto City, West Sumatra Province - Zumarni, Zumarni; Ningrum, Melani Puspa; Harahap, Anwar Efendi; Rodiallah, Muhamad; Handoko, Jully; Yendraliza, Yendraliza (Fakultas Peternakan Universitas Jambi, 2026)
Background: Selecting the right breeding stock in livestock farming plays a crucial role in population growth programs. Reproductive performance is a key indicator of success in cattle farming, influenced by both genetic and environmental factors Purpose: This study aims to determine the reproductive performance of several beef cattle breeds in Sawahlunto City, West Sumatra Province. Methods: The study employed a survey method with data collection conducted through purposive sampling. The data obtained are presented descriptively and quantitatively, showing mean values and standard deviations. To identify differences in reproductive performance across various beef cattle breeds, a Completely Randomized Design (CRD) was utilized, followed by analysis using Duncan’s Multiple Range Test (DMRT). The observed parameters included: Service per Conception (S/C), Conception Rate (CR), Days Open (DO), and Calving Interval (CI). Results: The results indicated that the S/C and CR values for beef cattle in Sawahlunto City are categorized as good. The DO and CI values for Bali cattle were superior compared to PO (Ongole Grade) and Simmental cattle. Conclusion: It can be concluded that bali cattle in Sawahlunto city exhibit superior reproductive performance compared to PO and Simmental cattle.